Reflective thoughts about violent media content – development of a bilingual self-report scale in English and German. Issue 6 (1st November 2020) - Bartsch, Anne; Scherr, Sebastian; Mares, Marie-Louise; Oliver, Mary Beth
ABSTRACT: This study investigates audiences' reflective thoughts about violent media content with the aim of developing a bilingual self-report scale in English and German. Scale development was based on an item pool of statements derived from previous qualitative interviews about individuals' reflection and meaning-making of violent media content. Two survey samples from the US ( N = 431) and Germany ( N = 412) rated their agreement with these statements, with an example of violent fiction, violent nonfiction, or the most recent violent content they had seen in mind. Factor analysis of the data revealed five main dimensions including reflective thoughts about: (1) human cruelty and suffering from violence, (2) own or close others' experiences with violence, (3) moral complexities of violence, (4) the true story behind violent content, and (5) strategies learned for dealing with violence in real life. Scale items selected to represent these five dimensions showed convergent validity with eudaimonic media experiences and perceived realism as well as comparable measurement properties across the two countries (US and Germany). Results are discussed with regard to the role of reflective thoughts as potential buffer against negative effects of exposure to media violence.